Epitope-tagged and phosphomimetic mouse models for investigating natriuretic peptide-stimulated receptor guanylyl cyclases - Egbert, Jeremy R.; Uliasz, Tracy F.; Lowther, Katie M.; Kaback, Deborah; Wagner, Brandon M.; Healy, Chastity L.; O’Connell, Timothy D.; Potter, Lincoln R.; Jaffe, Laurinda A.; Yee, Siu-Pok (Frontiers in Molecular Neuroscience, 2022)
The natriuretic peptide receptors NPR1 and NPR2, also known as guanylyl cyclase A and guanylyl cyclase B, have critical functions in many signaling pathways, but much remains unknown about their localization and function in vivo. To facilitate studies of these proteins, we developed genetically modified mouse lines in which endogenous NPR1 and NPR2 were tagged with the HA epitope. To investigate the role of phosphorylation in regulating NPR1 and NPR2 guanylyl cyclase activity, we developed mouse lines in which regulatory serines and threonines were substituted with glutamates, to mimic the negative charge of the phosphorylated forms (NPR1-8E and NPR2-7E). Here we describe the generation and applications of these mice. We show that the HA-NPR1 and HA-NPR2 mice can be used to characterize the relative expression levels of these proteins in different tissues. We describe studies using the NPR2-7E mice that indicate that dephosphorylation of NPR2 transduces signaling pathways in ovary and bone, and studies using the NPR1-8E mice that indicate that the phosphorylation state of NPR1 is a regulator of heart, testis, and adrenal function.